Additive engineering for improving the stability of tin-based perovskite (FASnI3) solar cells. (1st September 2022) - Li, Shaojie; Yang, Feng; Chen, Mengmeng; Yang, Jien; Jiang, Lulu; Sun, Yunjuan; Nirmala Graced, Andrews; Jain, Sagar M.; Liu, Hairui
Highlights: Doping strategies of tin-base perovskite solar cells are reviewed. Modulation of tin-base perovskite solar cells properties by employing dopants is highlighted. Current challenges and perspectives for future progress are given. Abstract: During the past few years, Tin (Sn)-based perovskites have been extensively investigated in the field of photovoltaics as promising candidates for new generation lead-free perovskite. Tin-based perovskites (ASnI3 ) present excellent photoelectric properties. However, there still remains a big concern over unsatisfactory stability. In reality, extensive efforts have been committed to improve the stability of perovskite active layer. In this review, a comprehensive understanding on defect formation, oxidation mechanism of Sn 2+ . Then, a detailed discussion on the recent advance the effect of additive engineering for the stability of FASnI3 PSCs, including antioxidants, 2D perovskite materials and functional passive molecular. Lastly, several key scientific issues and future research prospectives are proposed for achieving stable and high-performance Sn-based perovskite photovoltaics.